Numerical study of 3 × 1 SM-MM fiber combiner propagation properties with finite cladding. (14th October 2016) - Liu, Wenbo; Cao, Jianqiu; Guo, Shaofeng; Chen, Zilun; Xu, Xiaojun; Lu, Qisheng
Abstract: In this paper, the propagation properties of the 3  ×  1 single-mode-to-multimode (SM-MM) fiber combiner with finite cladding, is numerically investigated. It is found that the finite cladding has an indispensable effect on the property of the combiner. Because of the confinement of the finite cladding, both the taper ratio and transfer efficiency can be greatly improved. It is also found that high transfer efficiency can be realized by an output fiber core with the numerical aperture (NA) much smaller than the finite cladding NA. Besides, it is revealed that there should be an up-limitation of transfer efficiency, which decreases with the increment of the taper ratio of the combiner. The effects of other parameters on the transfer efficiency of the combiner are also investigated. The pertinent conclusions will have a significant impact on the study of the SM-MM fiber combiner.